Comparison of semen collected by electroejaculation and transrectal massage from Bali bulls (Bos javanicus) - Sarsaifi, Kazhal (2012)
The objective of this study was to compare the characteristics of Bali bull semen collected by electro-ejaculation (EE),and transrectal massage (RM), and to determine the effect of semen collection method on semen traits. Semen collection was performed on Bali bulls unaccustomed to being handled by EE or RM two times by each method. In both methods, the semen was evaluated for volume, pH, sperm concentration, percent of motile sperm, live, and normal morphology.Semen collected with the RM required more time (50 s, P <0.01) for obtaining a semen sample in RM compare with EE. However, higher volume and pH of the semen was obtained following EE, conversely, higher concentration was observed in semen collected with a RM. No differences in motility, viability and normal morpohology were obtained in fresh semen between methods. In conclusion, semen could be collected by RM from approximately 72% and 100% by EE from unaccustomed Bali bulls (Bos javanicus). Sperm morphology, viability and percent of motile sperm were not affected by the method of semen collection, but sperm were lower in volume from samples collected by RM.